A Qualitative Interview Study of Distributed Tracing Visualisation: A Characterisation of Challenges and Opportunities - Davidson, Thomas; Wall, Emily; Mace, Jonathan (IEEE Transactions on Visualization and Computer Graphics, 2023)
Distributed tracing tools have emerged in recent years to enable operators of modern internet applications to troubleshoot cross-component problems in deployed applications. Due to the rich, detailed diagnostic data captured by distributed tracing tools, effectively presenting this data is important. However, use of visualisation to enable sensemaking of this complex data in distributed tracing tools has received relatively little attention. Consequently, operators struggle to make effective use of existing tools. In this paper we present the first characterisation of distributed tracing visualisation through a qualitative interview study with six practitioners from two large internet companies. Across two rounds of 1-on-1 interviews we use grounded theory coding to establish users, extract concrete use cases and identify shortcomings of existing distributed tracing tools. We derive guidelines for development of future distributed tracing tools and expose several open research problems that have wide reaching implications for visualisation research and other domains.